Annotating Spike Protein Polymorphic Amino Acids of Variants of SARS-CoV-2, Including Omicron. (11th April 2022) - Mahardika, Gusti Ngurah; Mahendra, Nyoman B.; Mahardika, Bayu K.; Suardana, Ida B. K.; Pharmawati, Made
Abstract : The prolonged global spread and community transmission of severe acute respiratory syndrome virus 2 (SARS-CoV-2) has led to the emergence of variants and brought questions regarding disease severity and vaccine effectiveness. We conducted simple bioinformatics on the spike gene of a representative of each variant. The data show that a number of polymorphic amino acids are located mostly on the amino-terminal side of the S1/S2 cleavage site. The Omicron variant diverges from the others, with the highest number of amino acid substitutions, including the receptor-binding site (RBS), epitopes, S1/S2 cleavage site, fusion peptide, and heptad repeat 1. The current sharp global increase in the frequency of the Omicron genome constitutes evidence of its high community transmissibility. In conclusion, the proposed guideline could give an immediate insight of the probable biological nature of any variant of SARS-Cov-2. As the Omicron diverged the farthest from the original pandemic strain, Wuhan-Hu-1, we expect different epidemiological and clinical patterns of Omicron cases. On vaccine efficacy, slight changes in some epitopes while others are conserved should not lead to a significant reduction in the effectiveness of an approved vaccine.